Green Chemistry and Chemical Engineering - Han, Buxing; Wu, Tianbin; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2019)
This expanded, revised, and updated second edition of Innovations in Green Chemistry and Green Engineering provides a comprehensive introduction to the state-of-the-art in this key area of sustainability research. Processes that meet the objectives of green chemistry and chemical engineering minimize waste and energy use, and eliminate toxic by-products. Given the ubiquitous nature of products from chemical processes in our lives, green chemistry and chemical engineering are vital components of any sustainable future. Peer-reviewed articles from worldwide experts present the latest developments on topics ranging from organic batteries and green catalytic transformations to green nanoscience and nanotoxicology. Now under the leadership of distinguished Editors from the Chinese Academy of Sciences, this volume in the Encyclopedia of Sustainability Science and Technology, Second Edition, is an essential, one-stop reference for professionals in researchand industry. The book also fills the need for an authoritative course text in environmental and green chemistry and chemical engineering at the upper-division undergraduate and graduate levels.
1. Green Chemistry and Chemical Engineering, Introduction -- 2. Gas Expanded Liquids for Sustainable Catalysis -- 3. Green Catalytic Transformations -- 4. Green Chemistry Metrics: Material Efficiency and Strategic Synthesis Design -- 5. Green Chemistry with Microwave Energy -- 6. Nanotoxicology in Green Nanoscience -- 7. New Polymers, Renewables as Raw Materials -- 8. Organic Batteries -- 9. Oxidation Catalysts for Green Chemistry -- 10. Supercritical Carbon Dioxide (CO2) as Green Solvent -- Index.
Keywords: Green chemistry; Pollution; Chemistry, Technical; Chemistry, Organic; Inorganic chemistry; Catalysis; Green Chemistry; Pollution; Industrial Chemistry; Organic Chemistry; Inorganic Chemistry; Catalysis